Odpowiedzi

2010-02-13T20:24:20+01:00
(x-1)²-(y-3)²=(x-y)(x+y)
(x+2)/2-(y+4)/3=1 mnożę stronami przez 6
---------------------------------------------------------
x²-2x+1-y²+6y-9=x²-y²
3(x+2)-2(y+4)=6
--------------------------------
x²-2x+1-y²+6y-9-x²+y²=0
3x+6-2y-8=6
------------------------------------
-2x+6y=8
3x-2y=8 mnożę stronami przez 3
---------------------------------------
-2x+6y=8
9x-6y=24 dodaję równania stronami
--------------------------------------------
7x=32
x=32/7=4 i 4/7
podstawiam do równania 3x-2y=8
3*(32/7)-2y=8
96/7-2y=56/7
-2y=56/7-96/7
-2y=-40/7
y=20/7
y=2 i 6/7
--------------------------------
x=4 i 4/7
y=2 i 6/7